2010
DOI: 10.1016/j.ijantimicag.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Decline in the incidence of healthcare-associated methicillin-resistant Staphylococcus aureus (HA-MRSA) correlates with deceased antimicrobial consumption at a tertiary care hospital in Taiwan, 2001–2009

Abstract: The present study investigated the long-term impact of antibiotic use policy on the rates of consumption (expressed as daily-defined doses/1000 patient-days) of various parenteral antibiotics and on the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and the incidence of healthcare-associated MRSA (HA-MRSA) infection at a tertiary care hospital from 2001 to 2009. During this time, consumption of all antimicrobials for systemic use decreased by 33%. This change was driven by a 44% decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…2 In particular, time-series analysis accounts for the lag period between the implementation of a control measure and the response. Nonetheless, our study had several limitations that must be noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In particular, time-series analysis accounts for the lag period between the implementation of a control measure and the response. Nonetheless, our study had several limitations that must be noted.…”
Section: Discussionmentioning
confidence: 99%
“…1 In particular, infection with methicillin-resistant Staphylococcus aureus (MRSA) has increased rapidly during the last 15 years and is now a global health issue. 2 MRSA has a significant prevalence in Asia, the United States and elsewhere, and has a significant impact on mortality and morbidity in healthcare settings. 3 Recent studies have documented the epidemiology of healthcareassociated MRSA (HA-MRSA) and reported a recent trend of increasing prevalence in Europe and the USA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have also showed that controlled use of antibiotics leads to improved microorganism sensitivity 404 to antimicrobial agents (Lee et al, 2010;Takesue et al, 2010). The emergence of resistant pathogens and their negative impact on patient survival and healthcare costs need the evaluation of antimicrobial susceptibility in each health center and hospital in order to control infection.…”
Section: Patients a D M I T T E D T O Intensive Care Units (Icus)mentioning
confidence: 99%
“…Today, the emergence of multidrug-resistant (MDR) gramnegative and methicillin-resistant Staphylococcus aureus (MRSA) pathogens has become a major public health concern. Moreover, they negatively influence patients' outcomes and increase the length of hospital stays and healthcare costs (Giske et al, 2008;De Kraker et al, 2011;Resch, Wilke, Fink, 2009;Mulvey, Simor, 2009).Many studies have also showed that controlled use of antibiotics leads to improved microorganism sensitivity H. Hamishehkar, P. Shadmehr, A. Mahmoodpoor, S. O. Mashayekhi, T. Entezari-Maleki 404 to antimicrobial agents (Lee et al, 2010;Takesue et al, 2010). The emergence of resistant pathogens and their negative impact on patient survival and healthcare costs need the evaluation of antimicrobial susceptibility in each health center and hospital in order to control infection.…”
mentioning
confidence: 99%